IMPLEMENTATION OF PROJECT-BASED LEARNING IN STEM EDUCATION - Muhammad Arsyad; Ahmad Rathomi (Indonesian Journal of Education (INJOE), 2025)
This study aims to assess the effectiveness of project-based learning (PjBL) implementation in STEM education through a literature review at various levels of education in Indonesia. The method used is a systematic literature review of scientific articles, both national and international. The results of the study indicate that the integration of PjBL-STEM consistently improves learning outcomes, science literacy, and 21st-century skills such as critical thinking, creativity, collaboration, and communication. The main supporting factors for successful implementation include institutional support, teacher competence, student motivation, and adequate learning facilities. Meanwhile, the obstacles encountered include limited facilities, lack of teacher training, and challenges in integrating STEM across disciplines. Overall, the implementation of PjBL-STEM is highly recommended as an innovative learning strategy that is relevant to prepare students to face global challenges in the era of the industrial revolution 4.0.